USULAN KONTEN IKLAN DIGITAL PRODUK SMARTPHONE BERDASARKAN PERILAKU PENCARIAN DAN PEMBELIAN KONSUMEN MENGGUNAKAN DATA COOKIES PADA SITUS M-COMMERCE PT Y - NIM 14414024 , SOPANDI
Shopping daring behavior is raising along with internet development, condition of e-commerce’s competition in Indonesia, and the lower conversion rate product for smartphone category at PT Y’s site. This issue, urges them to increase their conversion rate. It can be reached by giving digital adsertising to customer. But at the recent ways, it does not consider consumer behavior yet. Whereas there possibility to increase purchasing when give a suitable ads to customers. This study investigates the consumer behavior of searching and purchasing to gain informations that can be used as a proposed digital adsvertising strategy. The empirical research is based on data cookies of customer’s transaction at m-commerce PT Y’s site. . This research construct a model for searching and purchasing behavior using latent class logistic regression model and define 21 hypothesis that will be examined. Searching behavior model is constructed using analysis sample consist of 99.574 observation datas and validated using holdout sample consist of 30.259 observation datas. Besides, purchasing behavior model is constructed using analysis sample consist of 3.311 observation datas and validated using holdout sample consist of 6.173 observation datas. Both of those validation process is using Press ’Q statistic and obtain p-value < 0,00001, which indicates that both of model prediction are better than random prediction. The findings from latent class logistic regression model suggest that there five latent class consumer based on searching behavior and five latent class consumer based on purchasing behavior. Both of them were integrated using cross tabulation method and generate five latent class consumer which are : directed buyer, search and deliberate consumer, hedonic browser, knowledge builder and impulsive buyer. Digital advertasing proposal made based on the characteristic of latent class consumer which increase purchasing probabilities composed of: ads attributes, number of ads, interval of ads, and number of product.